Implementation of the Storytelling Learning Model Assisted by Flashcard Media to Develop Speaking Skills of Fourth Grade Elementary School Students - Muhammad Sheva Sofbriaz Ashari; Beni Junaedi; Imamudin Imamudin (EDUJAVARE: International Journal of Educational Research, 2026)
Basic education has an important role in developing students' academic abilities and language skills. This study aims to analyze the influence of the storytelling learning model assisted by flashcard media on the speaking skills of grade IV students of SDN Beberan 2. The research approach method used is quantitative with the type of associative research. The research sample amounted to 36 students who were selected using saturated sampling techniques. Data collection techniques include observation, speaking skills tests, and questionnaires. Data analysis was carried out through validity, reliability, normality tests, paired sample t-test, and N-Gain tests. The results of the study showed an improvement in students' speaking skills after the application of the storytelling learning model assisted by flashcard media. The average pretest score of 45.97 increased to 83.61 in the posttest. The results of the paired sample t-test showed a significance of 0.000 < 0.05 which means there was a significant difference before and after treatment. Thus, the storytelling learning model assisted by flashcard media has been proven to be influential in improving the speaking skills of grade IV students of SDN Beberan 2.